FREIES ERMESSEN DALAM KONSEP NEGARA KESEJAHTERAAN - Damayanti, Gusti Ayu Ratih (Jurnal Advokasi, 2016)
In principle, there were two forms of administration policy, the policy of the administration of law and administrative policy that was not based on the law (the deviation from the law). Policy regulations based on law consists of rules policy based on Freies ermessen. Linkages Freies ermessen with the principle of legality was the principle of legality was the basis of legitimacy of government action and guarantee the protection of rights-the rights of the people. So it can be concluded that Freies ermessen does not conflict with the principle of legality because Freies ermessen category policy regulations based on law. Government officials were exempted from responsibility and accountability in the implementation of government affairs when the officials concerned to exercise authority and discretion and on behalf of the office and carried out in an environment of formal authority. Government officials charged with the responsibility and personal accountability in the case of officials concerned to personal error that caused it to deviate discretionary uses.